2008
DOI: 10.1159/000117394
|View full text |Cite
|
Sign up to set email alerts
|

Zarit Burden Inventory and Activities of Daily Living in the Behavioral Variant of Frontotemporal Dementia

Abstract: Background: Activities of daily living (ADL) and caregiver burden are known to have a major impact on the decision to institutionalize patients with Alzheimer’s disease (AD), yet little research has been done on these aspects in patients with frontotemporal dementia (FTD). Aim: To compare ADL and caregiver burden in FTD and in early-onset AD. Methods: We compared 26 FTD and 28 AD patients with respect to the Neuropsychiatric Inventory (NPI), Mini Mental State Examination, Mattis Dementia Rating Scale (MDRS), D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(103 citation statements)
references
References 60 publications
7
94
1
1
Order By: Relevance
“…In the current study, apathy generated the highest distress, followed by disinhibition, irritability and aggression, in agreement with de Vugt et al [2]. With the exception of apathy, such symptoms have been considered as part of a disruptive cluster of neuropsychiatric symptoms and, as such, they have been described as highly stressful by dementia caregivers [6,22,23]. Nevertheless, apathy has also been reported as highly stressful by family caregivers [7,24].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the current study, apathy generated the highest distress, followed by disinhibition, irritability and aggression, in agreement with de Vugt et al [2]. With the exception of apathy, such symptoms have been considered as part of a disruptive cluster of neuropsychiatric symptoms and, as such, they have been described as highly stressful by dementia caregivers [6,22,23]. Nevertheless, apathy has also been reported as highly stressful by family caregivers [7,24].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, Riedijk et al [4] showed that caregiver burden was higher in bvFTD than in AD patients and that the burden was higher when the duration of the degenerative disorder was short. In a study by Boutoleau-Bretonnière et al [6], caregiver burden was not associated with patients' functional or cognitive impairment but with patients' neuropsychiatric symptoms. In this latter study, bvFTD patients presented higher scores for apathy, disinhibition and eating disorders according to NPI scores.…”
Section: Introductionmentioning
confidence: 99%
“…those independent from the carer's report) influence burden of care. When this has been done, dementia subtype appears to be an important variable modulating burden: carers of patients with behavioural variant FTD (bvFTD) experience more stress and carer burden than carers of patients with other forms of dementia [1,3,6,14,15]. This increased stress may be related to the marked deficits in impulse control found more commonly in bvFTD than in AD patients [16,17,18,19].…”
Section: Introductionmentioning
confidence: 99%
“…It has been used in specific patient groups, for example those with frontotemporal dementia, 9 and as an outcome measure, for example in a trial of rivastigmine for apathy in Parkinson's disease. 10 The aims of this study were to: • measure caregiver burden using different ZBI versions at the initial assessment of patients referred to a dedicated cognitive disorders clinic with cognitive complaints • examine correlations between ZBI scores and patient age and scores on patient performancebased cognitive screening instruments • compare ZBI scores between different patient diagnostic groups to assess what utility the instrument might have as an informant-based cognitive screening instrument.…”
mentioning
confidence: 99%